[Pitch Lake, Trinidad and Tobago] - (:unkn) unknown (Mike Roberts, Berkeley, California, 2009)
Photo of the world famous pitch lake in Trinidad. One employee is seen digging pitch and others are loading railroad cars with pitch. "Trinidad, B.W.I. - 'Home of Angostura aromatic bitters'. The world famous pitch lake from which millions of tons of asphalt have been removed." Postcard No. c5351.
Colour: Green, Blue and Red Hues; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch; Asphalt industry--Trinidad and Tobago; Employees--Trinidad and Tobago; Railroad cars--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; [1960]; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Transportation--Trinidad and Tobago; Work; Working class--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Railroads--Trinidad and Tobago; Axes--Trinidad and Tobago; Tools--Trinidad and Tobago; Manual work--Trinidad and Tobago; Pitch Lake, The (La Brea)